Screening of toll-like receptor signaling pathway-related genes and the response of recombinant glutathione S-transferase A3 protein to thiram induced apoptosis in chicken erythrocytes - Jahejo, Ali Raza; Jia, Fa-Jie; Raza, Sayed Haidar Abbas; Shah, Mujahid Ali; Yin, Jiao-Jiao; Ahsan, Anam; Waqas, Muhammad; Niu, Sheng; Ning, Guan-Bao; Zhang, Ding; Khan, Ajab; Tian, Wen-Xia (Developmental and comparative immunology, 2021)
The expression of genes related to the Toll-like receptors (TLRs) signaling pathway were determined. Group A, B and C fed with basal diet and group D, E and F induced TD by feeding a basal diet containing 100 mg·kg-1 thiram. rGSTA3 protein was injected at 20 μg·kg-1 in group B, E and at 50 μg·kg-1 in C, F. Results suggested that lameness and death of chondrocytes were significant on day 14. TLRs signaling pathway related genes were screened based on the transcriptome enrichment, and validated on qPCR. IL-7, TLR2, 3, 4, 5, 7, 15, MyD88, MHC-II, MDA5 and TRAF6 were significantly (p < 0.05) expressed in group E and F as compared to group D on day 14 and 23. IL-7, MHCII, TRAF6, TLR3, TLR5, TLR7, and TLR15 determined insignificant in group D compared to group A on day 23. TD occur in an early phase and alleviated in the later period. rGSTA3 protein can prevent apoptosis and repair degraded chondrocytes.
Keywords: Chondrocytes; signální transdukce; Immunity; apoptóza; osteochondrodysplazie; thiram; Toll-Like Receptors; transkriptom; Immunity, Innate; nemoci drůbeže; rekombinantní proteiny; glutathiontransferasa; Protein; Signal Transduction; Avian Proteins; chondrocyty; Transcriptome; kur domácí; Glutathione Transferase; přirozená imunita; Erythrocytes; Chickens; toll-like receptory; zvířata; erytrocyty; Erythrocyte; Poultry Diseases; ptačí proteiny; Broiler; Osteochondrodysplasias; Tibial dyschondroplasia; Thiram; Recombinant Proteins; Apoptosis; Animals